(untitled) (Research, Society and Development, 2021)
The objective of this paper was to analyze the narratives of Basic Education teachers in the municipality of Novo Gama, GO regarding continuing education in times of pandemic, the challenges faced in working with virtual environments for teaching and learning and the perspectives for teaching in the period post-pandemic Covid-19. For this, this research adopted assumptions of qualitative research. Methodological procedures for documentary, bibliographic and empirical research were used. Documentary research and bibliographic research made it possible to contextualize the continuing education of teachers in the time of Covid-19. The empirical research made it possible to identify the challenges faced by teachers in the early years of the municipality of Novo Gama, GO when using virtual teaching and learning environments, as well as interpreting, through the essence of the interviewees’ messages, perspectives for teaching in the period post-pandemic Covid-19. In the results, three categories of content analysis are presented: the continuing education of teachers in times of Covid-19 pandemic; the challenges faced by teachers in working with virtual teaching and learning environments; teachers’ perspectives for post-pandemic education at Covid-19. Therefore, we conclude that, for the success of post-pandemic education, it is essential that teachers in the early years of Basic Education in the municipality of Novo Gama, GO acquire new knowledge for professional development, through continuous training, in order to enhance actions in virtual teaching and learning environments.